Integrating digital therapeutics for patients with mental illness into clinical practice: perspectives for US healthcare professionals - Brandon M. Kitay; David C. Mohr; Stephen M. Schueller (Frontiers in Public Health, 2026)
As the landscape of digital health tools has expanded, digital therapeutics have emerged as promising treatment options for various mental health conditions. Although digital therapeutics have demonstrated efficacy in prevention, treatment, and management of mental illness, adoption of these interventions in clinical practice remains low. Here, key questions for healthcare providers about implementation of digital therapeutics into US clinical practice are addressed, focusing on digital therapeutics for mental illness. The landscape of digital therapeutics is described and current barriers to adoption across stakeholders are discussed, considering patients, providers, and health systems. This article further highlights opportunities for development and population-based implementation of digital therapeutics.